Collaborative Malaria Surveillance Ending Outbreak In Merangin: Early Response By Academia And Muhammadiyah Community - Ghiffari, Ahmad; Risdiansyah, Risdiansyah; Qamariah, Nurul; Faradila, Faradila; Shalshabilla, Alysha Titania; Mukhtarudin, Kuntafie Al Haq; Safitri, Rizka Nabila; Prameswarie, Thia; Ramayanti, Indri; Asmalia, Resy (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT The Mass Blood Survey (MBS) conducted in August 2023 in Sungai Tebal Village, Jambi Province, in response to a malaria outbreak declared by the Regent of Merangin. The outbreak began with 52 confirmed malaria cases (50 Plasmodium vivax and 2 Plasmodium falciparum), indicating a substantial rise compared to previous years. The District Health Office, an academic institution, and community health partnered to carry out the MBS, which was launched six months after the index case. Prior to implementation, the team coordinated with local health authorities and community organization thus prepared for both rapid diagnostic testing (RDT) and public health education. A total of 33 individuals were tested, and all RDT results were negative, indicating no further local transmission. The findings underscored the importance of early detection, collaborative efforts, and sustained preventive strategies in malaria-endemic regions to avert future outbreaks. Keywords: Active Surveillance, Malaria Elimination, Outbreak Response, Rural Health, Integrated Control